-3(2x-4)+8x-5=

Simple and best practice solution for -3(2x-4)+8x-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2x-4)+8x-5= equation:


-3(2x-4)+8x-5=0

We simplify the equation to the form, which is simple to understand
-3(2x-4)+8x-5=0

Reorder the terms in parentheses
+(-6x+12)+8x-5=0

Remove unnecessary parentheses
-6x+12+8x-5=0

We move all terms containing x to the left and all other terms to the right.
-6x+8x=0-12+5

We simplify left and right side of the equation.
+2x=-7

We divide both sides of the equation by 2 to get x.
x=-3.5

See similar equations:

| (20x)/(((x^2)-4)^2) | | p^2+p-3= | | 2x×6=11x-3/4 | | (3-k)x+y+2=0 | | -a^2-11a-18= | | 2lnx-3ln(1/x)=10 | | 56/g= | | 0.4(5-04n)=3.2 | | y=-6/5x-3/8 | | x+0.07x=8025 | | .5lne^6=x | | x(7/100)=8025 | | 2x^2+32x+188=0 | | 6.4x-2.9=1.4a+12.1 | | -m^2-5m+50= | | 8z^2-48z=o | | Log(6x-8)=3 | | 6y-7-2y-3= | | (-3Y-7)+10= | | x-4=3(x+4) | | 0.20x+0.35(50)=28.5 | | 2tanx-3ctgx-1=0 | | 5x(2x+7)=0 | | 13/8-1/2= | | 6(X+9)-39= | | x+(x*.70)=16.12 | | -6h-19=17-4h | | 2a+10-4a-20=0 | | 7x-3y+x-2y= | | 9x-7=7x+23 | | y-12=4(x-6) | | -4.3(6.3x-4.18)=-58.56 |

Equations solver categories